Serum substance P level as a marker for subclinical rheumatoid arthritis activity. Issue 1 (31st December 2023) - Mohamed, Shimaa Borham; Elkenawy, Mohammed Fouad; Elsaid, Tamer Omar; Mashaly, Ghada El-Saeed
ABSTRACT: Background: Regular assessments of disease activity are essential to prevent the progression of rheumatoid arthritis (RA). Aim of the work: This study aimed to assess the utility of serum substance P (SP) level as a marker for RA activity and to establish the value of SP level for the diagnosis of subclinical RA activity. Patients and Methods: The study included three groups each 30. subject: Group 1 was with minimal or no disease, group 2 had moderate to severe disease activity and group 3 was healthy controls. RA patients were assessed using a Disease Activity Score-28 (DAS28) and power Doppler ultrasonography measurement of the synovitis total score. The serum substance P levels of study groups were assessed using ELISA technique. Results: Statistically significant difference in serum SP level was detected in RA patients compared to controls (p ≤ 0.001) and between different disease activity groups (p ≤ 0.001). The best cut off SP value to distinguish patients in subclinical activity active disease patients was 555.5 pg/ml. This had a diagnostic sensitivity, specificity, and accuracy of 96.7%, 80% and 88.3 %, respectively. Conclusion: Serum SP can be used as an indicator of RA disease activity even in those with subclinical activity.